2017
DOI: 10.1038/nprot.2017.115
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the small RNA interactome in bacteria using RIL-seq

Abstract: Small RNAs (sRNAs) are major post-transcriptional regulators of gene expression in bacteria. To enable transcriptome-wide mapping of bacterial sRNA-target pairs, we developed RIL-seq (RNA interaction by ligation and sequencing). RIL-seq is an experimental-computational methodology for capturing sRNA-target interactions in vivo that takes advantage of the mutual binding of the sRNA and target RNA molecules to the RNA chaperone protein Hfq. The experimental part of the protocol involves co-immunoprecipitation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 24 publications
3
101
0
Order By: Relevance
“…Further analysis of microarray data disclosed that higher levels of RyeB, CyaR, GcvB and RyhB in cells grown on pyruvate correlated with a decrease in the abundance of their known target mRNAs and/or their products of translation (for details, see Table S4). In addition, our gene expression data also revealed that a number of putative sRNA targets (see Table S5) envisaged in previous studies (Melamed et al 2018) had likewise lower abundance in cells grown on pyruvate and therefore were potentially controlled by new antisense mechanisms mediated by RyeB, CyaR, GcvB or RyhB in vivo. Moreover, as the post-transcriptional control of some genes by these sRNAs might affect protein abundance (e.g., regulation of SodB level by RyhB, Table S4), we additionally analyze 2D protein electrophoresis data to search for correlation between the level of the differentially expressed polypeptides and sRNAs predicted to control the corresponding protein-coding genes (Melamed et al 2018;Chao et al 2017).…”
Section: Known and Putative Srna Targets Differentially Expressed In supporting
confidence: 69%
See 1 more Smart Citation
“…Further analysis of microarray data disclosed that higher levels of RyeB, CyaR, GcvB and RyhB in cells grown on pyruvate correlated with a decrease in the abundance of their known target mRNAs and/or their products of translation (for details, see Table S4). In addition, our gene expression data also revealed that a number of putative sRNA targets (see Table S5) envisaged in previous studies (Melamed et al 2018) had likewise lower abundance in cells grown on pyruvate and therefore were potentially controlled by new antisense mechanisms mediated by RyeB, CyaR, GcvB or RyhB in vivo. Moreover, as the post-transcriptional control of some genes by these sRNAs might affect protein abundance (e.g., regulation of SodB level by RyhB, Table S4), we additionally analyze 2D protein electrophoresis data to search for correlation between the level of the differentially expressed polypeptides and sRNAs predicted to control the corresponding protein-coding genes (Melamed et al 2018;Chao et al 2017).…”
Section: Known and Putative Srna Targets Differentially Expressed In supporting
confidence: 69%
“…In addition, our gene expression data also revealed that a number of putative sRNA targets (see Table S5) envisaged in previous studies (Melamed et al 2018) had likewise lower abundance in cells grown on pyruvate and therefore were potentially controlled by new antisense mechanisms mediated by RyeB, CyaR, GcvB or RyhB in vivo. Moreover, as the post-transcriptional control of some genes by these sRNAs might affect protein abundance (e.g., regulation of SodB level by RyhB, Table S4), we additionally analyze 2D protein electrophoresis data to search for correlation between the level of the differentially expressed polypeptides and sRNAs predicted to control the corresponding protein-coding genes (Melamed et al 2018;Chao et al 2017). This analysis made it possible to expand the number of putative genes and their products (see Table S6) whose level might potentially be controlled by RyeB, CyaR, GcvB, RyhB via new post-transcriptional mechanisms during E. coli growth on alternative carbon sources.…”
Section: Known and Putative Srna Targets Differentially Expressed In supporting
confidence: 69%
“…1 ). This observation is consistent with the RNA-seq characterization of Hfq-dependent sRNA-mRNA interactions described by Melamed et al [ 9 , 21 ], in which approximately 60% of all described interactions occur in the middle of the coding regions.
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…Most sRNAs require an RNA-binding "matchmaker" protein, e.g., Hfq, to facilitate base pairing of the sRNA with its targets, a feature that is harnessed in a related technology, called RIL-seq (RNA interaction by ligation and sequencing). Here, sRNA-target pairs are cross-linked on Hfq, trimmed by ribonucleases, and ligated using T4 RNA Ligase (Melamed et al, 2018(Melamed et al, , 2016. Generation of cDNA and sequencing of the chimeric RNA allow for the global identification of sRNA-target interactions under selected conditions.…”
Section: Discussionmentioning
confidence: 99%